Reforming the Pension Reforms: Argentina and Chile - Rofman, Rafael; Fajnzylber, Eduardo; Herrera, German (2012)
This article describes the most recent pension reforms in Argentina and Chile. The previous reforms, implemented in the 1980s and 1990s, aimed to improve long-term fiscal sustainability and institutional design of the systems, shifting part of the social and economic risks away from the State and on to participants. In recent years, the authorities in both countries identified the main problems facing current pension systems as inadequate coverage for older adults and the low level of benefits. The two countries have responded differently, however, owing to institutional and political divergences. In Chile, a lengthy participatory process resulted in a wide-ranging reform targeting medium-term effects through carefully calibrated adjustments. In contrast, the reforms in Argentina were made through a succession of corrections, with little public discussion of their implications or effects on coverage and fiscal needs.